European SMEs and Resource Efficiency Measures: Firm Characteristics and Contextual Factors - Guglielmo Maria Caporale; Cristiana Donati; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates how access to finance and skilled workforce endowments affect the propensity of European small and medium sized enterprises (SMEs) to adopt different types of resource efficiency measures (REMs), possibly simultaneously. For this purpose, a Multinomial Logit model is estimated using data from the 2017 Flash Eurobarometer survey covering a large sample of European firms. The analysis is carried out first for the whole sample and then for clusters based on two contextual factors measured by the Ease of Access to Loans Index (EAL) and the European Skill Index (ESI). The findings suggest that the two firm characteristics considered lead to the adoption of more than one REM simultaneously. Moreover, the propensity to implement them is stronger in the case of firms located in countries with easier access to financial resources, whilst the workforce skill-set appears to be a less important factor in this context.
Keywords: G32; O16; Q40; 330; resource efficiency measures; financing; SMEs; workforce skills